Unveiling the Dynamics: Trends and Crises of Administrative Accountability in Bangladesh - Hossan, Md. Alomgir; Mahmud, Md. Sultan; Alom, Md. Jahangir (MultiTech Publisher, 2024)
This paper examines the trends and crises surrounding administrative accountability in Bangladesh from 2009 to the present. Bangladesh, characterized by its complex political landscape and socio-economic challenges, faces significant hurdles in ensuring transparency and integrity within its administrative institutions. Drawing upon a comprehensive review of academic literature, official reports, and empirical evidence, this study analyzes the evolution of administrative accountability mechanisms and explores the factors shaping their effectiveness. Key themes include the role of oversight bodies, legal frameworks, and institutional structures in promoting or impeding accountability within the Bangladeshi administrative system. The paper also investigates prominent crises and scandals that have exposed vulnerabilities in the accountability framework, highlighting their origins, impacts, and implications for governance. Through rigorous analysis and synthesis of existing literature, this study aims to contribute to scholarly discourse and policy debates on administrative accountability in Bangladesh. By identifying critical challenges and opportunities, it provides a foundation for informed decision-making and strategic interventions to strengthen accountability mechanisms in the country.